Fetal Abdominal Cystic Lesion: A Diagnostic Dilemma and Prognostic Challenge-Report of Two Cases of Mesentric Lymphangioma with Review of Literature - Minakshi, Rohilla; Sujata, siwatch; Muneer, Abbas Malik; Tanuja, Muthyala; Ram, Samujh; Narasimhan, Kannan (Journal of Women's Reproductive Health, 2021)
Fetal mesentric lymphangioma, a congenital fetal abdominal cystic malformation has a rare occurrence. Antenatal detection, its differential diagnosis, prenatal management options and parental counseling regarding postnatal prognosis of such a case are thus rarely discussed. We report two cases of antenatally detected fetal cystic abdominal mass with a provisional diagnosis of abdominal lymphangioma. Postnatally one of the neonates developed features of intestinal obstruction and required surgical intervention. Intra-operative findings and histopathology report confirmed a mesentric lymphangioma. The other neonate had associated subcutaneous lymphangiectasia in left lumbar region, left sided inguinal hernia, undescended testes and was asymptomatic postnatally and managed conservatively.
Keywords: Fetal abdominal cyst; Lymphangioma; subcutaneous lymphangiectasia.